Another Note on Dilworth's Decomposition Theorem. (10th January 2013) - Pijls, Wim; Potharst, Rob
Abstract : This paper proposes a new proof of Dilworth's theorem. The proof is based upon the minflow/maxcut property in flow networks. In relation to this proof, a new method to find both a Dilworth decomposition and a maximal antichain is presented.